2014
DOI: 10.1038/ncomms4035
|View full text |Cite
|
Sign up to set email alerts
|

Natural wetland emissions of methylated trace elements

Abstract: Natural wetlands are well known for their significant methane emissions. However, trace element emissions via biomethylation and subsequent volatilization from pristine wetlands are virtually unstudied, even though wetlands constitute large reservoirs for trace elements. Here we show that the average volatile fluxes of selenium (o0.12 mg m À 2 day À 1 ), sulphur (o37 mg m À 2 day À 1 ) and arsenic (o0.54 mg m À 2 day À 1 ) from a pristine peatland are considerable and consistent over two summers. We compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 51 publications
0
68
0
Order By: Relevance
“…Microbial methylation for conversion of soluble selenium oxyanions into volatile selenium compounds has been proposed for bioremediation of selenium-contaminated agricultural drainage water and seleniferous soils (59,(129)(130)(131)(132)(133). Microbial volatilization opens perspectives for recovering selenium via the gas phase, which is thus free from cells and other metal contaminants.…”
Section: ϫmentioning
confidence: 99%
“…Microbial methylation for conversion of soluble selenium oxyanions into volatile selenium compounds has been proposed for bioremediation of selenium-contaminated agricultural drainage water and seleniferous soils (59,(129)(130)(131)(132)(133). Microbial volatilization opens perspectives for recovering selenium via the gas phase, which is thus free from cells and other metal contaminants.…”
Section: ϫmentioning
confidence: 99%
“…Phytoplankton uptake of Se (VI) is thought to be inhibited in seawater by high sulfate concentrations as Se (VI) uptake involves membrane sulfate transporters (Fournier et al, 2010;Winkel et al, 2015). This pathway is therefore substantially lower than Se (IV) uptake into marine algae (Price et al, 1987;Vriens et al, 2014). Thus, given the similar concentrations of Se (VI) and Se (IV) in ocean surface waters, uptake of Se (VI) should not be significant.…”
Section: Introductionmentioning
confidence: 99%
“…Bas Vriens et al . reported an increased rate of As methylation with increasing temperatures in both surface water and air suggesting that the methylation of As is temperature dependent32. It is also reported that at high pH, the presence of organic matter and moderate moisture and temperature would favor microbial-mediated As biotransformation33.…”
Section: Discussionmentioning
confidence: 97%